2007
DOI: 10.21273/jashs.132.2.158
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cluster Thinning on Return Bloom, Nut Quality, and Concentrations of Potassium, Nitrogen, and Non-structural Carbohydrates

Abstract: Alternate bearing pecan trees [Carya illinoinensis (Wangenh.) C. Koch] were hand-thinned annually to 1, ≤2, or ≤3 fruit/cluster or not thinned when the ovule was about one-half expanded. Return bloom was monitored on (1) vegetative shoots, (2) bearing shoots without a second growth flush in the terminal position on 1-year-old branches, (3) bearing shoots without a second growth flush in the lateral position on 1-year-old branches, and (4) bearing shoots with a second growth f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
1
11
1
Order By: Relevance
“…Additionally, sugar signaling also plays key roles in developmental processes such as flowering (Gibson, 2005), in which complex interplay between phytohormones and sugars affects each other (Leon and Sheen, 2003). In the case of pecan, it is clear that sugars are intimately involved in one or more processes controlling floral initiation (Smith and Waugh, 1938;Sparks, 1974Sparks, , 1975Wood, 1989, Wood et al, 2004Worley 1979aWorley , 1979b with their role being expressed in association with successful vernalization and subsequent floral evocation (Wetzstein and Sparks, 1983;Wood, 1989Wood, , 1995; however, sugars are not the sole factor driving pistillate flower initiation nor AB (Rohla et al, 2007a(Rohla et al, , 2007bSmith et al, 2007). Timely use of bioregulators may provide the means of affecting key downstream floral initiation processes through effects on sugar-based chromatin modulation (Gibson, 2003(Gibson, , 2005Koch, 1996; such as that occurring during floral vernalization and evocation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, sugar signaling also plays key roles in developmental processes such as flowering (Gibson, 2005), in which complex interplay between phytohormones and sugars affects each other (Leon and Sheen, 2003). In the case of pecan, it is clear that sugars are intimately involved in one or more processes controlling floral initiation (Smith and Waugh, 1938;Sparks, 1974Sparks, , 1975Wood, 1989, Wood et al, 2004Worley 1979aWorley , 1979b with their role being expressed in association with successful vernalization and subsequent floral evocation (Wetzstein and Sparks, 1983;Wood, 1989Wood, , 1995; however, sugars are not the sole factor driving pistillate flower initiation nor AB (Rohla et al, 2007a(Rohla et al, , 2007bSmith et al, 2007). Timely use of bioregulators may provide the means of affecting key downstream floral initiation processes through effects on sugar-based chromatin modulation (Gibson, 2003(Gibson, , 2005Koch, 1996; such as that occurring during floral vernalization and evocation.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy and horticultural potential of bioregulators to control the ''on'' and ''off'' flowering phases of pecan trees has not been reported despite considerable circumstantial evidence that endogenous phytohormones are involved in floral initiation processes (Barnett and Mielke, 1981;Rohla et al, 2007aRohla et al, , 2007bWood, 1982Wood, , 1984aWood, , 1984bWood, , 1991Wood, , 2003Wood and McMeans, 1981;Wood et al, 2003). A variety of natural and synthetic bioregulators are efficacious for control of floral initiation processes in several polycarpic perennial crops and involve timely use of floral promoters [generally ethephon and P-Ca and NAA or GA 4 in certain situations (Looney et al, 1985)] in ''on'' years to promote return flowering the following ''off'' year and use of floral inhibitors [gibberellic acids (GA 3,4,7 ) (Greene, 2000) and auxin analogs (e.g., NAA) in certain cases] in ''off'' years to decrease subsequent year flowering.…”
mentioning
confidence: 99%
“…Uniform cropping among years with good nut quality was possible on 'Pawnee', but the optimum cropload was a moving target, probably reflecting changes in tree canopy size among years and environmental conditions during the growing season. The ability of 'Pawnee' to achieve uniform cropping between years with abundant production supports work (Rohla et al, 2007a) indicating that 'Pawnee' has characteristics of a low alternate-bearing cultivar (Rohla et al, 2007b). The alternate-bearing reputation of 'Pawnee' appears to be associated with inadequate fruit thinning when trees are overloaded (Smith and Fig.…”
Section: Discussionmentioning
confidence: 63%
“…Phytohormones are candidates for long-distance signals such that gibberellins and auxin inhibit floral induction, whereas cytokinins promote floral induction (Bangerth, 2009;Wood, 2011). In pecan, non-structural carbohydrate concentrations in roots were implicated in pistillate flower differentiation (post-floral induction) (Malstrom, 1974;Smith and Waugh, 1938;Sparks and Brack, 1972;Wood, 1989Wood, , 1991Worley, 1979), but later work demonstrated that abundant stored non-structural carbohydrates were not related to return bloom (Rohla et al, 2007a(Rohla et al, , 2007bSmith et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation